The Influence of Halal Marketing, Exposure, WOM and Brand Image on Interest in Halal Cosmetics - fatia, Amalia; Kurniawati, Kurniawati (Universitas Islam Lamongan, 2025)
This study aims to examine the influence of Halal Marketing, Exposure, Brand Image, and Word of Mouth (WOM) on consumer intention to purchase halal cosmetics in Indonesia, with Halal Awareness and Attitude as mediating variables. Data were collected through an online survey with 352 respondents from the millennial and Gen Z generations in Indonesia. Data analysis used Structural Equation Modeling (SEM) with the AMOS 24 program. The results showed that Halal Marketing and Exposure had a significant effect on Halal Awareness, which affected the intention to purchase halal cosmetics. Brand Image also had a significant effect on Attitude, which increased consumer purchase intention. In addition, WOM significantly influenced consumer Attitude, emphasizing the importance of recommendations in forming positive attitudes towards halal cosmetics. These findings suggest that a positive brand image and effective halal marketing strategies can increase consumer awareness and positive attitudes towards halal products, which ultimately drives their purchase intention. Managerial implications emphasize the importance of building a strong brand image and utilizing effective marketing strategies with educational content to increase consumer purchase intention towards halal cosmetics.